Compósitos de matrizes poliméricas com mantas aleatórias de fibras vegetais de sisal e de coco - Darros, Andressa Bella (Universidade Federal de São Carlos, 2013)
The search for new materials in order to alleviate the environmental problems have encouraged the use of raw materials of natural origin to replace, at least partially, to synthetically produced. Vegetable fibers may be used for incorporation into composites of polymer matrices, being renewable, biodegradable and non-toxic. However, generally vegetable fibers exhibit lower mechanical and thermal properties due to the components present in the fiber (cellulose, hemicellulose and lignin) when compared with high performance fibers such as glass fibers and carbon. In general, polymeric matrices can be of three types; thermoset, thermoplastic and thermoplastic biodegradable. In this paper, polymeric matrices and composites of polymer matrices were obtained with the use of random webs of coconut fibers and sisal fibers by compression molding in a hydraulic press. This study involved a comparative study of composites molded polymer matrices with their epoxy resin, polypropylene (PP), and polyhydroxybutyrate (PHB) without fiber. Were performed some types of thermal and mechanical tests for all molded materials. The techniques used were differential scanning calorimetry (DSC), thermogravimetry (TG), dynamic mechanical thermal analysis (DMTA) in bending mode, and mechanical tests of flexural and tensile before and after conditioning in air chamber, with temperature and humidity. The results of flexural tests to room temperature for composites of epoxy resin and PHB values were similar in the resistance of materials when compared to the respective polymer matrix without fibers. The composite of PP / sisal fibers showed a higher resistance when compared to PP without fiber, related to good fiber-matrix interaction. Flexural and tensile tests of specimens after the conditioning chamber for acclimatization showed decreases in resistance of all materials, being more pronounced for composites due to high moisture absorption of natural fibers. The results of DMTA before conditioning showed an increase in E' of the composites of epoxy resin as compared to the epoxy resin without fibers, because the fibers restrict the movement of the molecular chains located at the interfacial region. Relative to PP, composite PP / sisal fibers had an E' greater. The PHB without fibers showed a modulus greater than the composites containing coconut fiber and sisal fibers. DMTA analyzes performed on materials post conditioning decreased in modules, due to weakening of the fiber-matrix interactions.
Polymeric matrices composites with vegetable fibers random mat of sisal and coconut
Keywords: materiais compósitos; polímeros; fibras; compósitos; fibras vegetais; análises; ensaios mecânicos; composites; polymers; natural fibers; analysis; mechanical tests; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::POLIMEROS